The Right Ventricle in Pulmonary Hypertension - Wessels, Jeroen N.; Celant, Lucas R.; de Man, Frances S.; Noordegraaf, Anton Vonk (Seminars in Respiratory and Critical Care Medicine, 2023)
The right ventricle plays a pivotal role in patients with pulmonary hypertension (PH). Its adaptation to pressure overload determines a patient's functional status as well as survival. In a healthy situation, the right ventricle is part of a low pressure, high compliance system. It is built to accommodate changes in preload, but not very well suited for dealing with pressure overload. In PH, right ventricular (RV) contractility must increase to maintain cardiac output. In other words, the balance between the degree of RV contractility and afterload determines stroke volume. Hypertrophy is one of the major hallmarks of RV adaptation, but it may cause stiffening of the ventricle in addition to intrinsic changes to the RV myocardium. Ventricular filling becomes more difficult for which the right atrium tries to compensate through increased stroke work. Interaction of RV diastolic stiffness and right atrial (RA) function determines RV filling, but also causes vena cava backflow. Assessment of RV and RA function is critical in the evaluation of patient status. In recent guidelines, this is acknowledged by incorporating additional RV parameters in the risk stratification in PH. Several conventional parameters of RV and RA function have been part of risk stratification for many years. Understanding the pathophysiology of RV failure and the interactions with the pulmonary circulation and right atrium requires consideration of the unique RV anatomy. This review will therefore describe normal RV structure and function and changes that occur during adaptation to increased afterload. Consequences of a failing right ventricle and its implications for RA function will be discussed. Subsequently, we will describe RV and RA assessment in clinical practice.
Keywords: right ventricle; right atrium; pulmonary hypertension; risk stratification; cardiac magnetic resonance imaging; echocardiography